Students’ Self-Regulation as Correlate of Academic Achievement in Biology in Public Secondary Schools in Orlu Education Zone, Imo State, Nigeria - Ndidi Angelina Ononuju; Chidinma Eberechukwu Okwara-Kalu; Annabel Uchechukwu Obinna-Akakuru; Ordua Victor Ndubuisi (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
The study investigated students’ self-regulation as a correlate of academic achievement in Biology in public secondary schools in Orlu Education Zone, Imo State, Nigeria. The study which adopted a correlation research design was guided by two research questions and hypotheses. The population for the study was 24,600 female students and male students. The sample size for the study was 200 female students and male students, from 5 intact classes of 40 students each, selected through a simple random sampling technique. One instrument, the “Students’ Self-Regulation Questionnaire” (SSRQ) was used for data collection. The instrument was validated by three lecturers in the Department of Educational Psychology, Alvan Ikoku College of Education, Owerri. The reliability of the instrument was established using test-retest method which yielded a coefficient of 0.86. Pearson’s Product Moment Correlation Coefficient (r) was used to answer the research questions and test the null hypotheses at 0.05 level of significance. Results showed a moderate extent to which acceptance of responsibility and controlling one's learning correlate with academic achievement in Biology in public secondary schools in Orlu Education Zone. In addition, there is no significant correlation between acceptance of responsibility and academic achievement in Biology in public secondary schools in Orlu Education Zone. It was concluded that students’ self-regulation correlates with academic achievement in Biology in public secondary schools as students’ acceptance of responsibility and controlling their own learning for their learning are considered important correlates